Sources of Information in Adoption of Sustainable Agricultural Practices as Perceived by Farmers in Sindh Province of Pakistan - Muhammad Ismail Kumbhar; Har Bakhsh Makhijani; Shuhabuddin Mughal; Hameeda Masood Shah; Naseer Ahmed Abbasi (Journal of Basic & Applied Sciences, 2015)
Agriculture is the backbone of Pakistan’s economy in terms of providing food and employment and foreign exchange earnings. It contributes 21.9 percent to the gross domestic product (GDP). The importance of sustainable agriculture practices for the farmers to a large extent depends upon the effective sources of information. It is believed that farmers do not often make visit to the research stations, however, they obtained required knowledge from different sources like mass media, fertilizer agency, fellow farmers, radio, television, extension personnel and contact farmers. It is imperative to communicate sustainable agriculture practices to the farmers through various sources of information. This study used a descriptive research methodology the universe of study consisted of six districts of Sindh province comprising Larkana, Naushehro Feroze, Shaheed Benazirabad, Sanghar, Mirpurkhas and Badin. A sample of 180 farmers was randomly selected for the study. A well structured interview schedule was used to collect information from the small farmers on their personal and socio-economic characteristics and sources of information. The study found that about 36.11% of the respondents were youth having age group (26-35 years), while 66.67% of the respondents were married, however a large percentage (44.44%) maintained a range of small farmers having land 13-25 acres of land and 66.67% of the respondents having their primary education. In addition 66.67% of the respondents having farming experience between 6 to 10 years. The results of the study showed that the most frequently used sources of information about Sustainable Agriculture were Television Broadcast, Neighboring Farmer, Fertilizer and Herbicide Dealer and Seed Dealer, while slightly over half the farmers reported using information about Sustainable Agriculture from Public Extension Agent, Private Extension Agent, Research Workers, Farm Magazine and Publications, Local Newspapers, Relatives and Extension Materials. On the basis of the results and conclusion drawn from the study it is recommended that Government should establish farmers radio and television station for dissemination of the agricultural programs for sustainable agriculture in Sindh province. Sustainable agriculture programs should be broadcast through television and radio programs. Neighbor farmers and fertilizer herbicide dealers should be educated for sustainable agriculture practices.